Exploring the impact of elexacaftor-tezacaftor-ivacaftor treatment on opinions regarding airway clearance techniques and nebulisers: TEMPO a qualitative study in children with cystic fibrosis, their families and healthcare professionals. Issue 1 (7th October 2022) - Almulhem, Maryam; Harnett, Nuala; Graham, Stephanie; Haq, Iram; Visram, Shelina; Ward, Christopher; Brodlie, Malcolm
Abstract : Background: Cystic fibrosis (CF) is a genetic condition caused by variants in the cystic fibrosis transmembrane conductance regulator (CFTR ) gene that primarily impacts the lungs. Treatments historically have been symptomatic to improve airway clearance and treat infection. However, CFTR modulator drugs have recently been developed that target the underlying defect. The triple combination of elexacaftor-tezacaftor-ivacaftor (ETI) was approved in 2020 in England for over 80% of people with CF aged over 12 years and in 2022 extended to those over 6 years. ETI treatment is associated with substantial improvements in lung function. The experience of children with CF starting on ETI or their views regarding future treatments have not been well studied. This study aimed to explore the opinions of children with CF, their parents/carers and healthcare professionals (HCPs) on the impact of ETI, airway clearance techniques (ACTs) and nebulised treatments. Methods: Semistructured qualitative interviews were performed with 10 children with CF, 7 parents/carers and 10 HCPs. Audio recordings were transcribed and analysed using reflexive thematic analysis. Results: Four main themes were identified: 'Kaftrio changed my life', 'Your entire life is dictated by the CF timetable', 'Simplifying treatment-hopes and fears' and 'Kaftrio is a game-changer' along with several subthemes and an overarching theme of 'I still can't get my head around how three tablets can do what Kaftrio done'. Conclusions: Despite the highly positive impact of ETI on the health of children with CF some concerns remain about the longer-term outcomes of reducing ACTs or nebulised treatments. ETI has prompted a shift in treatment for many and offers an opportunity to personalise approaches.